Half‐dose ganciclovir preemptive treatment of cytomegalovirus infection after pediatric allogeneic hematopoietic stem cell transplantation. Issue 3 (9th June 2016) - Ju, H.Y.; Kang, H.J.; Hong, C.R.; Lee, J.W.; Kim, H.; Park, K.D.; Shin, H.Y.; Park, J.D.; Choi, E.H.; Lee, H.J.; Ahn, H.S.
Abstract: Background: Ganciclovir (GCV) has been widely used as preemptive therapy after hematopoietic stem cell transplantation (HSCT), although bone marrow suppression is a known accompaniment, with secondary infection or bleeding as potential complications. Our aim was to evaluate clinical outcomes in pediatric patients with low cytomegalovirus (CMV) antigenemia levels using half the dosage of GCV generally given preemptively. Methods: Patients received half doses of intravenous GCV (5 mg/kg once daily, 6 days/week) at CMV antigenemia levels <10/200, 000 cells. At higher levels of CMV antigenemia, conventional doses of GCV (5 mg/kg every 12 h) were administered. Results: A total of 130 patients were evaluated, detecting CMV antigenemia in 87 (66.9%). Of these patients, 74 (85.1%) were treated preemptively with half‐dose GCV, which proved effective as sole therapy in 51 (68.9%). CMV retinitis developed in 4 patients, 2 of whom initially were given half‐dose GCV. All infections resolved successfully, with no CMV‐related deaths. CMV seropositivity in recipients was the only significant risk factor for positive CMV antigenemia (hazard ratio [HR] = 10.05, P = 0.046). Compared with half‐dose GCV administration, conventional GCV dosing resulted in a higher rate of severe neutropenia, defined as absolute neutrophil count <0.5 × 10 9 /L (HR = 4.30, P = 0.015). Conclusion: Half‐dose GCV therapy at CMV antigenemia levels <10/200, 000 cells is an effective and safe means of preemptively treating pediatric CMV infection after HSCT.